The Life Course of 20th-Century Lyon Silk Workers. A Pilot Study - Elizabeth Wroten; Tamara Hareven (Historical Life Course Studies)
At the time of her death in October 2002, Dr. Tamara Hareven was in the process of completing a large cross-cultural examination of the global declines in the silk and textile industries. A small sample of her interview data transcripts from canuts in Lyon have, more than 20 years after her death, been translated into English and coded for themes as a pilot study of a larger data set. Six themes emerged from the participants' data.  Participants sensed that the industry was disappearing, that the industry was something that was looked at as a historical artifact to be studied rather than a profession, and that there was not enough being done to encourage young people to enter the industry. Gender disparities within the industry continued to a lesser extent than before the 20th century began, but still seemed profound, especially as girls who were recruited for apprenticeships were often minors when they were moved away from their families. The apprenticeship conditions continued to be less than desirable well into the 20th century. Economically, the silk industry is often poorly paid and vulnerable to economic crises as fashion and world economics change. Large social changes often had impacts on the family life of the silk worker families. Finally, just as economics tended to ebb and flow for the silk industry, so did the labor conditions.